Jazz art in Ukraine: historical context - Olianych, Valentina; Olianych, Larysa (My University, 2021)
The article examines cultural changes in society, from the NEP period to the present day, using the example of the phenomenal phenomenon of jazz art, which made a real breakthrough in cultural life. The emergence of new jazz orchestras, instrumental dance music, and elements of theatricalization introduced new phenomena into the spiritual life of society. During the period of the new economic policy, the concept of «jazz» among the average population of the country was presented as a phenomenon of commercial music. The Soviet government constantly tried to control cultural life, putting it in an ideological framework, dictating rules and putting obstacles. Jazz was interpreted as a «bourgeois» weapon of ideological struggle for the consciousness of the Soviet people. Jazz was listened to with pleasure, gradually it acquired the term «mass popular art», which absorbed various trends of the XX century: beat, pop, smash hit, pop, musical, rock, rap, rhythm and blues, soul, folk, jazz. In the context of historical research, it is worth noting that jazz in Ukraine over the centuries is gradually becoming a unifying ideological innovation that goes deeper into society and, regardless of race, religion, ethnic origin, unites millions of people.
Olianych V. Jazz art in Ukraine: historical context / Valentina Olianych, Larysa Olianych // Knowledge, Education, Law, Management, 2021. – № 7(43). – Vol. 2. – P. 50–54.
Keywords: джаз, джазове мистецтво, джаз в Україні, джаз-оркестри, культура, історія мистецтва, джазові напрями, музика; jazz, jazz art, jazz in Ukraine, jazz orchestras, culture, art history, Jazz trends, music